Effect of Aqueous Extract of Moringa oleifera Leaves on Some Production Performance and Microbial Ecology of the Gastrointestinal Tract in Growing Rabbits - El-Kholy, K.H.; Barakat, Safaa A.; Morsy, W.A.; Abdel-Maboud, K.; Seif-Elnaser, M.I.; Ghazal, Mervat N. (Pakistan Journal of Nutrition, 2017)
Objective: This study was conducted to determine the effect of aqueous Moringa oleifera leaf extracts (AMOLE) on growth performance and carcass characteristics of rabbits. Methodology: A total number of 64 mixed sex growing APRI rabbits aged 5 weeks and weighing 661.8±8.08 g was assigned randomly into four treatment groups to evaluate the effect of aqueous Moringa oleifera leaves extract (AMOLE) added in water. The four experimental groups were as follows: The control group (G1) received basal diet and water without any supplementation, while groups 2, 3 and 4 received basal diet and water supplemented with 30 (G2), 60 (G3) and 90 (G4) mL AMOLE/L drinking water, respectively. The study was lasted for 8 weeks during the growing period, from weaning age (at 5 weeks) to marketing age (at 13 weeks). Results: The results revealed that Moringa leaves extract at its highest levels significantly (p